2023
DOI: 10.3390/molecules28207084
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Antifungal Activity of Some Novel Phenylthiazole Derivatives Containing an Acylhydrazone Moiety

Yao Tian,
Jinchao Shi,
Xiaoqian Deng
et al.

Abstract: Crop fungal diseases pose a serious threat to global crop production and quality. Developing new and efficient fungicides is an important measure to control crop diseases. Phenylthiazole was found to be an excellent antifungal skeleton based on our previous study on the structural optimization and biological activity of the natural product thiasporine A. To find new fungicides, 45 phenylthiazole derivatives containing an acylhydrazone moiety were designed and synthesized by the principle of active substructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Thiasporine A ( Figure 1 ) is a heterocyclic natural product initially isolated from marine-derived Actinomycetospora chlora SNC-032 by MacMillan in 2015 [ 15 ]. In our previous work, we synthesized several series of thiasporine A derivatives with potent antifungal activity and demonstrated that phenylthiazole was a promising antifungal activity skeleton [ 16 ]. Notably, Shi [ 17 ] introduced an 1,3,4-oxadiazole thione into phenylthiazole to synthesize compound E1 ( Figure 1 ), exhibiting the most excellent antifungal activity against S. sclerotiorum with an EC50 value of 0.22 μg/mL, which was superior to that of the commercial fungicide Carbendazim (EC 50 = 0.70 μg/mL).…”
Section: Introductionmentioning
confidence: 99%
“…Thiasporine A ( Figure 1 ) is a heterocyclic natural product initially isolated from marine-derived Actinomycetospora chlora SNC-032 by MacMillan in 2015 [ 15 ]. In our previous work, we synthesized several series of thiasporine A derivatives with potent antifungal activity and demonstrated that phenylthiazole was a promising antifungal activity skeleton [ 16 ]. Notably, Shi [ 17 ] introduced an 1,3,4-oxadiazole thione into phenylthiazole to synthesize compound E1 ( Figure 1 ), exhibiting the most excellent antifungal activity against S. sclerotiorum with an EC50 value of 0.22 μg/mL, which was superior to that of the commercial fungicide Carbendazim (EC 50 = 0.70 μg/mL).…”
Section: Introductionmentioning
confidence: 99%